Conflict Resolution in Sharia Business Bankruptcies in Indonesia: Ethical and Legal Challenges - Siswanto, Siswanto; Achmad, Adang Darmawan; Qotadah, Hudzaifah Achmad; Ramli, Mohd Anuar (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: The objective of this study is to analyze and provide a description of the reasons why bankruptcy disputes in the Islamic economy continue to fall under the jurisdiction of the Commercial Court, a Special Court subordinate to the District Court. Additionally, it seeks to determine the ramifications of divergent Sharia norms and principles in business bankruptcy disputes involving Sharia contracts when resolved in accordance with conventional laws and regulations. A descriptive qualitative approach was adopted with the primary data obtained through several relevant sources. Data analysis was carried out using a legal approach, a sociological approach, and a philosophical approach. This study concluded that, in spite of the fact that it has been almost 18 years since the Commercial Court was established, the truth remains that it continues to have jurisdiction over insolvency cases in the Sharia commercial business sector. The absolute authority of the Religious Courts to address Sharia economic issues was expanded by Law No. 3 of 2006, which was passed in 2006. This leaves a significant question mark regarding the challenges and opposing norms and principles that may arise regarding insolvency disputes in Sharia economic enterprise if they are decided and handled using conventional general procedures and rules. Additionally, the Constitutional Court decision Number 93/PUU-X/2012 is exceedingly significant. It ends the dualistic way of resolving disputes in Sharia economics. It clarifies that Sharia economic disputes decided in the District Court do not have binding legal force if they are looked at further. Therefore, business bankruptcies and companies employing Sharia contracts are included in this disagreement and other commercial conflicts. Abstrak: Penelitian ini bertujuan untuk meneliti dan mendeskripsikan mengapa sampai saat ini sengketa kepailitan pada ekonomi syariah masih menjadi kewenangan Pengadilan Niaga yang merupakan Pengadilan Khusus dibawah Pengadilan Negeri, dan apa akibatnya terhadap perbedaan norma dan prinsip Syariah pada sengketa kepailitan usaha yang berdasarkan akad Syariah jika diselesaikan melalui hukum dan undang-undang yang masih bersifat konvensional. Jenis penelitian ini adalah deskriptif kualititaf dengan menggunakan pendekatan hukum, pendekatan sosiologis, dan pendekatan filosofis. Kajian ini berkesimpulan bahwa meskipun sudah hampir 18 tahun Pengadilan Niaga berdiri, faktanya Pengadilan Niaga masih memiliki yurisdiksi atas perkara kepailitan di sektor bisnis komersial syariah. Kewenangan absolut Pengadilan Agama untuk menangani masalah ekonomi Syariah diperluas oleh UU No. 3 tahun 2006, yang disahkan pada tahun 2006. Hal ini menyisakan tanda tanya besar mengenai tantangan dan pertentangan norma dan prinsip yang mungkin timbul terkait sengketa kepailitan di bidang ekonomi syariah jika diputuskan dan ditangani dengan menggunakan prosedur dan aturan umum konvensional. Selain itu, putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 sangat signifikan. Putusan ini mengakhiri cara dualistik dalam penyelesaian sengketa ekonomi syariah. Putusan tersebut menjelaskan bahwa sengketa ekonomi syariah yang diputus di Pengadilan Negeri tidak memiliki kekuatan hukum mengikat jika ditinjau lebih lanjut. Oleh karena itu, kepailitan bisnis dan perusahaan yang menggunakan kontrak Syariah termasuk dalam perselisihan ini dan konflik komersial lainnya.